PROSES PENGAMBILAN KEPUTUSAN GURU DALAM KASUS DILEMA ETIS - , Arifin ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Empirical research on teachersâ decision-making process in the case of ethical dilemmas is rare. Researchers were more interested in examining other aspects of the role of teachers on aspects such as motivation, competence, learning methodologies, and performance of teachers in general. In fact, as educational leaders, teachers are often faced with ethical dilemmas cases that require them to be able to take the best decisions for students. Any decision taken by the teacher in response to an ethical dilemma cases will bring a huge impact to the development and future learners. Therefore this research needs to be done to fill the existing research gap. This study aims to 1) identify the ethical paradigm used by teachers in decision-making, 2) identify the sources of teacher judgment in decision-making, and 3) analyze the steps that teachers take in the decision-making process when faced with an ethical dilemma cases. This type of research is a descriptive study using a questionnaire method of data collection in the form of a hypothetical scenario. Respondents of this study were 58 teachers of SMK Muhammadiyah Wonosari Gunungkidul. Data were analyzed with descriptive statistical analysis methods. Based on the data analysis and discussion, it can be summarized as follows: First, ethical paradigm that is used by the majority of teachers of SMK Muhammadiyah Wonosari in making decisions when faced with ethical dilemmas mild cases is an ethic of care, whereas in the case of heavy ethical dilemmas cases, they used ethical paradigm of justice. Second, the source of the consideration that is often used by teachers in decision-making is the principal, counselor teachers, parents, school rules, and the vice principal. Third, the steps used by teachers in decision-making is still limited to the step to understand the case, consult, and make a decision, without making detailed implementation steps.